The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/17476348.2021.1987891
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacterial lung disease caused by Mycobacterium avium complex - disease burden, unmet needs, and advances in treatment developments

Abstract: Introduction: Nontuberculous mycobacterial (NTM) lung disease (LD) is the most common clinical manifestation of NTM infection and is a growing health concern. Up to 85% of NTM-LD cases are caused by Mycobacterium avium complex (MAC). Increased awareness of NTM-LD caused by MAC is needed as patients with this disease experience substantial burden and unmet treatment needs. Areas covered: This review provides clinicians and regulatory and healthcare decision makers an overview of the clinical, economic, and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 134 publications
0
21
0
1
Order By: Relevance
“…Upon inhalation, the liposomes reach the lungs where they can enter alveolar macrophages where the MAC bacteria live whereas free amikacin has a limited ability to cross the membranes of mammalian cells, reducing its ability to achieve sufficient anti-mycobacterial levels inside the infected cells. The liposomal formulation of amikacin has shown better in vitro and in vivo efficiency in the delivery of the drug into macrophages, airways, and lung tissue compared to its non-liposomal counterpart [85][86][87].…”
Section: Deposition Of Inhaled Therapeutic Agents In the Respiratory ...mentioning
confidence: 99%
“…Upon inhalation, the liposomes reach the lungs where they can enter alveolar macrophages where the MAC bacteria live whereas free amikacin has a limited ability to cross the membranes of mammalian cells, reducing its ability to achieve sufficient anti-mycobacterial levels inside the infected cells. The liposomal formulation of amikacin has shown better in vitro and in vivo efficiency in the delivery of the drug into macrophages, airways, and lung tissue compared to its non-liposomal counterpart [85][86][87].…”
Section: Deposition Of Inhaled Therapeutic Agents In the Respiratory ...mentioning
confidence: 99%
“…Recent epidemiology studies have revealed a rising incidence of non-tuberculous Mycobacterium pulmonary disease (NTM-PD) both regionally and globally, with a higher prevalence in Asian countries than the Western world. 76 The presence of comorbidities is a poor prognostic factor leading to a higher hospitalization and mortality rate. 77 The latest treatment guideline endorses the use of amikacin liposome inhalation suspension (ALIS) in refractory Mycobacterium avium complex (MAC)-PD, which is defined as remaining sputum culture-positive after 6 months of guideline-based therapy (GBT).…”
Section: Other Respiratory Infections Mac Pulmonary Diseasementioning
confidence: 99%
“…Recent epidemiology studies have revealed a rising incidence of non‐tuberculous Mycobacterium pulmonary disease (NTM‐PD) both regionally and globally, with a higher prevalence in Asian countries than the Western world. 76 The presence of comorbidities is a poor prognostic factor leading to a higher hospitalization and mortality rate. 77 …”
Section: Other Respiratory Infectionsmentioning
confidence: 99%
“…A recent meta-analysis of 14 studies from Asia, Europe, and North America estimated the 5-year all-cause mortality for MAC-LD was 27% [ 14 ]. Failure to respond to treatment is common, and approximately 20–40% of MAC-LD cases are refractory to treatment [ 15 18 ]. Refractory MAC-LD is associated with increased healthcare resource utilization (HCRU) [ 19 ] and a reported 2-year mortality of 45% [ 20 ].…”
Section: Introductionmentioning
confidence: 99%